Endoscopic Discectomy Versus Open Microdiscectomy: Systematic Review for Lumbar Disc Herniation Treatment - Eric Wijaya; Alhoi Hendry Henderson; I Nyoman Ehrich Lister (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Lower back pain (LBP) is a widespread global issue, with nearly 80% of the population expected to experience at least one episode in their lifetime. Disc herniation is closely linked to disc degeneration, a process accelerated by aging. As individuals age, fibro chondrocytes in the disc undergo senescence, leading to reduced proteoglycan production. This reduction results in disc dehydration and collapse, increasing stress on the annulus fibrosus. Consequently, tears and fissures develop, facilitating the herniation of the nucleus pulposus. Chronic symptoms often emerge gradually due to the repetitive mechanical stress applied to the disc. Percutaneous endoscopic lumbar discectomy (PELD) has been shown to yield better outcomes compared to traditional methods, particularly in terms of reduced blood loss, smaller incisions, and shorter bed rest duration. However, conclusive guidelines comparing endoscopic to open approaches remain limited, underscoring the need for rigorous systematic reviews and risk-of-bias assessments to clarify the relative efficacy and safety profiles of these techniques. Method: We developed the methodology for this systematic review following criteria outlined in the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 checklist. Additionally, we conducted a preliminary risk-of-bias assessment for the included studies to ensure more rigorous evaluation of their quality. Result: Both PELD and conventional surgery significantly decrease ODI and VAS scores postoperatively. However, the control group shows a more substantial reduction in scores than the PELD group. Despite this, PELD is effective in treating herniated lumbar discs, offering advantages such as minimal postoperative pain, faster recovery, and reduced blood loss. Due to heterogeneity in outcome measures and follow-up durations across the included studies, a formal meta-analysis was not performed. Conclusion: While PELD appears to improve surgical outcomes and reduce oxidative stress, further high-quality randomized trials are needed to confirm these benefits and establish standardized selection criteria.